Exploring patterns of forest governance quality: Insights from forest frontier communities in Zambia's Miombo ecoregion. (December 2020) - Nansikombi, Hellen; Fischer, Richard; Kabwe, Gillian; Günter, Sven
Highlights: Mean scores for forest governance indicators are generally low. Governance scores of different arrangements do not differ significantly. Factors considerably reflect the indicators from the GFI framework. Formal and customary rules and institutions are clearly differentiated on the ground. There is a high variability of governance processes within and across provinces. Abstract: Good forest governance is a prerequisite for sustainable forest management and the successful implementation of initiatives that aim to reduce deforestation and forest degradation. The necessity for good governance is high in Zambia's Miombo ecoregion, which is characterised by persistent deforestation that also threatens forest-dependent livelihoods. Zambia has adopted policies and initiatives to improve forest governance. We use the Governance of Forests Initiatives (GFI) indicator framework from the World Resource Institute in 24 communities in the Miombo ecoregion to examine Zambia's status in this respect. The Wilcoxon rank test is applied to compare the de facto governance performance between different arrangements with differing tenures and restrictions to forest access and use. We employ factor analysis to test the applicability of the GFI framework based on community perceptions and cluster analysis to examine whether patterns of community clusters reflect the governance structure of the provincial local government administration. Comparative results show low mean scores for governance indicators, which do not differ significantly between arrangements. This indicates a weak de facto forest governance performance across arrangements, specifically characterised by an inadequate enforcement of rules and restrictions on use, insufficient institutional financial, human and technical capacities and unsatisfactory participatory land use planning and forest policy-making processes. We recommend support for financial and technical institutional capacities combined with coordination mechanisms to permit the satisfactory enforcement of forest rules. Frequent monitoring, apprehension and graduated sanctions are proposed as part of the rule enforcement procedures. Stringent de jure requirements coupled with capacity building for participatory land use planning and public policy participation also need to be adopted. This would also contribute towards achieving targets for Zambia's climate change response strategy, national development plan 2017–2021 and REDD + preparedness phase. The factor analysis largely confirms the GFI framework's suitability for governance analysis on the ground since factors generally mirror GFI indicators. However, because de facto governance processes sometimes do not precisely reflect thematic areas of the framework, we warn against the use of single indicators to exclusively represent a thematic area. Similarly, specific attention has to be paid to customary rules and institutions when applying the GFI framework because compared to the framework, the respective aspects are more clearly differentiated on the ground. Cluster analysis reveals a high variability of governance processes within and across provinces. Decentralization measures should take into account clusters that may in some cases follow administrative levels or in other cases go beyond the established administrative boundaries. Specifically, initiatives to integrate customary structures into the decentralized governance structure should take these regional differences into account.